TEACHING AND LEARNING THE CLARINET IN CHILDREN’S MUSIC AND ART SCHOOLS: METHODS, APPROACHES, AND CHALLENGES - Abdurayimov Faxriddin Muxammadali o‘g‘li (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
This article explores the process of teaching and learning the clarinet in children’s music and art schools. It focuses on pedagogical methods, individualized approaches, and the practical challenges faced by both teachers and students in mastering the instrument. Special attention is given to the importance of breath control, posture, and technical exercises, as well as the psychological and physical development stages of young learners. The article also highlights solutions to common difficulties encountered during clarinet instruction in early music education settings.